2013
DOI: 10.1007/s00402-013-1897-0
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty after high tibial osteotomy: a registry-based case–control study of 1,036 knees

Abstract: Previous studies have described technical difficulties during the TKA procedure after HTO, but they have found no adverse effects on the outcome. Our study supports previous research, and despite the slightly higher revision rate, TKA after HTO provides satisfactory results when compared to routine primary TKAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 14 publications
2
31
0
5
Order By: Relevance
“…Therefore, a subsequent conver-sion from HTO to TKA due to progression of osteoarthritis might be expected, whereas progression of arthritis or implant failure are considered an adverse event in UKA surgery. To our knowledge, this study constitutes the largest direct comparison of TKA following UKA with TKA following HTO based on a nationwide registry (Pearse et al 2012) and expands upon a range of recent nationwide registry studies comparing the survival of either TKA following UKA or TKA following HTO with primary TKA (Niinimäki et al 2014, Badawy et al 2015, Robertsson and W-Dahl 2015, Leta et al 2016, El-Galaly et al 2018, 2019, Lewis et al 2018. Due to inconsistent adjustment for confounding, a direct comparison of the results in the current literature might be affected by residual confounding, which could result in acceptance of a false causal relationship (Kyriacou and Lewis 2016).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, a subsequent conver-sion from HTO to TKA due to progression of osteoarthritis might be expected, whereas progression of arthritis or implant failure are considered an adverse event in UKA surgery. To our knowledge, this study constitutes the largest direct comparison of TKA following UKA with TKA following HTO based on a nationwide registry (Pearse et al 2012) and expands upon a range of recent nationwide registry studies comparing the survival of either TKA following UKA or TKA following HTO with primary TKA (Niinimäki et al 2014, Badawy et al 2015, Robertsson and W-Dahl 2015, Leta et al 2016, El-Galaly et al 2018, 2019, Lewis et al 2018. Due to inconsistent adjustment for confounding, a direct comparison of the results in the current literature might be affected by residual confounding, which could result in acceptance of a false causal relationship (Kyriacou and Lewis 2016).…”
Section: Discussionmentioning
confidence: 90%
“…Nationwide registry studies have investigated the survival of either TKA following UKA or TKA following HTO compared with primary or revision TKA. They have reported an increased risk of revision in TKA following UKA (Robertsson and W-Dahl 2015, Leta et al 2016, Lewis et al 2018, El-Galaly et al 2019 while no consensus regarding the influence of HTO on the survival of a subsequent TKA has been reached (Niinimäki et al 2014, Badawy et al 2015, Robertsson and W-Dahl 2015, El-Galaly et al 2018). However, a direct comparison of the survival estimates from these studies is prone to confounding by indication due to a range of unadjusted baseline characteristics associated with the survival of TKA, such as implant constraints and hospital volume of arthroplasty surgeries (Jasper et al 2016).…”
mentioning
confidence: 99%
“…However, both had poorer survivorship rates compared to primary TKA (Pearse et al 2012). The Finnish Arthroplasty Register found a slightly higher revision rate for TKA after HTO, but concluded that these were satisfactory results (Niinimaki et al 2014). In a study from the Swedish knee arthroplasty register, Robertsson and W-Dahl (2015) recently found an increased risk of revision for TKA after previous UKA or HTO, but they would not argue against the use of HTO in selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…After reading the articles, Sixteen of the 340 citations were selected for the meta-analysis. The characteristics and data of these 16 studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] are shown in Tables 1 and 2.…”
Section: Search Resultsmentioning
confidence: 99%